(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article talks about socio-psychological problems of effective education during the student periods, positive psychology and development of positive moods. Specific features of positive thinking of students: everyday life, positive attitude to the future, peoples` moods, independence, concept of happiness, self-awareness, positive moods of students`, effectiveness of training in education as the main criterion for raising the quality of education, spiritual and mental conditions, affecting positive thinking of some psychological issues is analyzed by focusing on factors such as self-satisfaction, mental stress, inability to apply self-affirmations, external pressures, moodiness, negativism, inability to engage in interpersonal relationships and dissatisfaction of conditions.